Potensi Pembuatan Batako dari Limbah Fly Ash dan Bottom Ash - Widya Hastuti Afris; Riskawati; C. Elisa Martina Katili; Muh Nurkhalis (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
PT. XYZ is a company engaged in seaweed processing, where the production process uses coal as boiler fuel to generate steam power for driving production activities. Coal combustion produces two types of waste, namely Fly ash and Bottom ash. Long-term accumulation of Fly ash and Bottom ash waste may require large storage space and cause environmental problems. This study aims to utilize Fly ash and Bottom ash waste (FABA) as an additive material in the production of concrete blocks (batako) and to calculate the production cost per batch. The research method used to address the problem was an experimental method. Based on the test results of the concrete blocks, it can be concluded that Fly ash and Bottom ash waste is feasible to be used as a mixture material in concrete block production with quality level II, using a composition of 300 g cement, 1500 g sand, and 1500 g Bottom ash. The test results showed a unit weight of 2.5 kg/unit, a compressive strength of 60 kN, and a water absorption percentage of 30%. The total production cost for producing concrete blocks using Fly ash and Bottom ash waste was Rp. 1,057,808 per batch, or Rp. 3,340 per unit